Efisiensi Operasional Bank Umum Syariah - Budi gautama Siregar; Aswadi Lubis; Muhammad Salman (Jurnal Penelitian Ekonomi Akuntansi, 2023)
The purpose of this study was to analyse and describe the effect of Non-Performing Financial, Capital Adeuacy Ratio and bank size on the operational efficiency of Islamic Commercial Banks for the period 2017-2022. This research approach is quantitative with the source of data used is secondary, namely quarterly reports from Islamic Commercial Banks. In determining the sample used with purposive sampling technique, so that the data that met the criteria were 8 banks with 20 quarters from 2017-2022. Data analysis was carried out through statistical methods, namely descriptive analysis, classical assumptions hypothesis testing with the help of the Eviews application. The results showed that Non-Performing Financial affects the level of operational efficiency of Islamic Commercial Banks while Capital Adequacy Ratio and bank size cannot affect the operational efficiency of banks.